A comparative assessment of energy demand and life cycle costs for additive- and subtractive-based manufacturing approaches. (August 2020) - Ingarao, Giuseppe; Priarone, Paolo C.
Highlights: Additive- and subtractive-based manufacturing approaches are compared. Cumulative energy demand and life cycle costs are assessed. Empirical models to quantify the performance metrics are proposed. Decision-support charts for identifying the optimum approach are developed. Abstract: The applicability domain of Additive Manufacturing (AM) processes, apart from technological and quality results, relies on environmental and cost performance. These aspects still need to be better understood. To this aim, comparative analyses with conventional manufacturing routes are needed. In this paper, empirical cost and energy requirement models are suggested to assess subtractive- (machining) and additive- (Electron Beam Melting) based manufacturing approaches for the production of Ti-6Al-4V components. A life-cycle perspective is adopted, and all the steps from the input material production to the post-AM processing operations and the use phase are included. The analyses have been carried out considering the shape of the component, the light-weighting capabilities and the utilization time as the main factors of influence. The proposed modelling effort has allowed different decision-support charts, which are suitable for identifying the most energy-efficient or economically-advantageous manufacturing approach, to be obtained. The results have revealed that, for the considered case study, EBM could be a more energy-efficient approach than conventional machining, even without re-designing the component, due to the higher efficiency in raw material usage. As far as cost is concerned, the additive-based approach only becomes the preferable solution when the cost savings during the use phase are accounted for.